Biodiversity at Patna Bird Sanctuary, Jalesar with Special Reference to Migratory Birds - Arun Kumar Singh; Arun Kumar Singh; Anu Singh; Jyoti Chaturvedi; Amit Kumar Jangid; Harshit Sharma (Revista Electronica de Veterinaria, 2024)
Indian subcontinent plays host to a number of migratory birds in summers as well as winters. It is estimated that over hundred species of migratory birds fly to India, either in search of feeding grounds or to escape the severe winter of their native habitat. About 200,000 birds of 300 different bird species frequent the sanctuary. More than 106 species of migratory and resident birds are known to have their resting habitats around the lake. Patna bird sanctuary was created in 1991 in order to protect and conserve the natural habitation and surroundings and also the marine vegetation for the migratory birds, as well as for the local people of the region. The term migration is used to describe movements of populations of birds or other animals. There are three types of migrants. One way to look at migration is to consider the distances traveled. The pattern of migration can vary within each category, but is most variable in short and medium distance migrants. The origin of migration is related to the distance traveled. The migratory birds at Patna Bird Sanctuary include Lesser whistling-duck, Graylag goose, Comb duck, Ruddy shelduck, Gadwall, Eurasian wigeon, Indian spot-billed duck, Northern shoveler, Northern pintail, Green-winged teal, Common pochard, Ferruginous duck, Baer's pochard, Tufted duck, Indian peafowl, Common quail, Black francolin, Gray francolin, Little grebe, Asian openbill, Woolly-necked stork, Black-necked stork, Little cormorant, Great cormorant, Purple heron, Cattle egret, Indian pond-heron, Black-headed ibis, Red-naped ibis, Eurasian spoonbill, Black-shouldered kite, Egyptian vulture, Booted eagle, Bonelli's eagle, Shikra, Black kite, Eurasian coot, Sarus crane, Black-winged stilt, Black-tailed godwit, Laughing dove, Greater coucal, Rose-ringed parakeet, Plum-headed parakeet, Long-tailed shrike, Black drongo, Rufous treepie, Ashy-crowned sparrow-lark, Bengal bushlark, Red-vented bulbul, Plain leaf warbler, Ashy prinia, Plain prinia, Common babbler, Oriental magpie-robin, Brahminy starling, Common myna, Bank myna, Purple sunbird, Indian silver bill, Scaly-breasted munia. Richness and diversity of water birds are highest at the end of April. This is because; migratory birds converge at Patna WLS from other areas before the spring migration. It appears that Patna WLS is not only an important refuge but also a stopover site for winter migrants returning to their breeding quarters from peninsular and central India. Waders and other marsh species are far more abundant at the end of April. The migratory birds represent the economic importance of that particular area and faunal biodiversity along with health of ecosystem.